Assessment of Virtual Reality Distraction Techniques on Dental Anxiety in Children During Tooth Extractions - M. I, Sheefaa.; Reddy, B. Aishwarya; R, Ramesh (Journal of Neonatal Surgery, 2025)
Background: Managing dental anxiety in children is a significant challenge in pediatric dentistry. Virtual Reality (VR) distraction techniques have emerged as a potential method to alleviate anxiety and improve cooperation during procedures. Aim: To evaluate the effectiveness of VR distraction techniques in reducing dental anxiety among children undergoing tooth extractions. Materials and Methods: A total of 30 children (15 in the test group using VR distraction and 15 in the control group without VR distraction) participated in the study. Anxiety levels were assessed using the Modified Venham Anxiety Scale (MVAS) before and after treatment. The study analyzed anxiety reduction, cooperation levels, and procedural success rates. Results: The test group (VR distraction) showed a significant reduction in anxiety scores, with the mean MVAS score decreasing from 6.2 ± 1.5 preoperatively to 2.8 ± 1.2 postoperatively (p < 0.05). In contrast, the control group showed a less pronounced reduction, from 6.1 ± 1.6 to 5.0 ± 1.3 (p > 0.05). Additionally, 80% of children in the test group exhibited good cooperation compared to 40% in the control group. Conclusion: VR distraction significantly reduces dental anxiety and improves patient cooperation in pediatric tooth extractions, making it a promising non-pharmacological intervention.